Educação midiática na formação de professores de geografia da Unipampa : caminhos para a inovação pedagógica - Silva, Diego Mattos da (2025)
The current situation exposes a disturbing reality in the lives of individuals, since, in the globalized society in which they are inserted, there is a great volume and speed in the information that is made available. In this way, being able to cope with this situation in the best possible way proves to be of great value. Thus, it is assumed that the school, as a training institution, must be prepared to meet this demand. In this scenario, this research aims to identify the elements that make Media Education viable as a path to pedagogical innovation in the initial training of Geography teachers. To this end, the guiding documents of the Unipampa/UAB Geography degree course were analyzed. This work is characterized as a qualitative approach, basic, descriptive research with a bibliographic and documentary method. Content analysis was used as a methodological tool, associated with the positive and negative aspects of internal and external influences present in the SWOT matrix methodology. The results indicate the presence of circumstances that foster the development of media and information competences by undergraduates. On the other hand, the existing limitations are also clear, such as the lack of clarity in the development of Media Education, as well as the reduced workload for this purpose. The findings also highlight the need for stronger action on the part of the state, in collaboration with higher education institutions, with the aim of promoting media and information literacy among future teachers, so that they can integrate it into their classroom practice.